Coral Reef Fish Community in the Waters of Osi Island West Seram Maluku - Sara Haumahu; Indra Komalia; Frederik Rijoly (Politeknik Negeri Sambas, 2026)
Coral reef fish are a crucial fishery resource in tropical waters, including Maluku. Information regarding the species of coral reef fish caught in the waters of Osi Island, West Seram District, is still limited. This study aimed to identify the coral reef fish species captured in the waters of Osi Island and its surroundings based on their meristic and morphometric characteristics. The research was conducted in December 2024, utilizing 12 fish specimens caught by local fishermen. Species identification was carried out through the observation of meristic and morphometric characters, which were then matched with identification keys and taxonomic literature. The results revealed seven coral reef fish species belonging to five genera: Lutjanus, Pterocaesio, Myripristis, Sargocentron, and Siganus. The species identified included Lutjanus rufolineatus, Lutjanus fulviflamma, Pterocaesio tesselata, Myripristis berndti, Myripristis murdjan, Sargocentron tiereoides, and Siganus fuscescens. Pterocaesio tesselata and Siganus fuscescens were the most commonly found species, with three specimens of each. The meristic and morphometric characteristics of all specimens fell within the ranges described in previous studies for these species. This study contributes additional baseline information on the diversity of coral reef fish in Maluku waters.